Modelling of floor joists contribution to the lateral stiffness of RC buildings designed for gravity loads. (15th August 2016) - Montuori, R.; Nastri, E.; Piluso, V.
Highlights: A model to evaluate the "equivalent beam" in RC buildings designed for gravity loads is proposed. The ratio between the torsional stiffness of beams and the flex. stiffness of the joists is considered. The number of joists for the equivalent beam is used both for single and multi storey buildings. Abstract: The work herein presented is aimed to the estimation of the contribution of floor joists acting as an "equivalent beam" in RC buildings designed for gravity loads where the deck has often no beams in the direction parallel to the warping of the floor joists. Regarding this issue a simplified theoretical model has been preliminarily developed. This model accounts for the ratio between the torsional stiffness of transverse beams supporting the floor joists and the flexural stiffness of the floor joists. The relation obtained has been applied to compute the number of collaborating joists defining the equivalent beam for a sample of single-story and multi-storey buildings with different geometrical characteristics. Successively, by means of a wide comparison between the lateral stiffness of a structural model based on the "equivalent beam" and the 3D structural model including all the joists, a correction factor is proposed to improve the accuracy of the formulation based on the simplified theoretical model.